2023
DOI: 10.3390/su152014725
|View full text |Cite
|
Sign up to set email alerts
|

Achieving SDG 4, Equitable Quality Education after COVID-19: Global Evidence and a Case Study of Kazakhstan

Naureen Durrani,
Gulmira Qanay,
Ghazala Mir
et al.

Abstract: This study investigates the impact of two years of emergency distance schooling on achieving Sustainable Development Goal (SDG) 4—equitable quality education, both globally and in Kazakhstan. The study used a qualitative research design. Individual semi-structured interviews were conducted with 30 teachers and 30 parents, while focus group discussions (FGDs) were utilised to gather the perspective of 28 students. The conceptual framework developed puts effective pedagogy at the heart of quality distance educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
(112 reference statements)
0
9
1
Order By: Relevance
“…The shift to online schooling underscored the necessity for heightened parental communication, while the closure of physical schools brought about a notable transformation in home-school communication dynamics (Durrani et al, 2023; Spear et al, 2023). Treating parents as equal partners in learning and guiding them through regular interactions became crucial as families took on more responsibility for schooling (Kaminskienė et al, 2021; Rigby et al, 2020).…”
Section: Literature Review: School Leadership During the Pandemicmentioning
confidence: 99%
See 3 more Smart Citations
“…The shift to online schooling underscored the necessity for heightened parental communication, while the closure of physical schools brought about a notable transformation in home-school communication dynamics (Durrani et al, 2023; Spear et al, 2023). Treating parents as equal partners in learning and guiding them through regular interactions became crucial as families took on more responsibility for schooling (Kaminskienė et al, 2021; Rigby et al, 2020).…”
Section: Literature Review: School Leadership During the Pandemicmentioning
confidence: 99%
“…While there is a lack of specific studies on school leaders’ perspectives and practices during COVID-19, insights can be drawn from existing literature. An extensive quantitative study found that 97% of schools transitioned to distance and online education without sufficient preparation or infrastructure (Bokayev et al, 2021b), highlighting the necessity for teacher professional development in digital instruction, especially in rural schools where teachers faced significant challenges with digital learning (Durrani et al, 2023). Teachers have reported limited autonomy in academic matters, stress from class observation, and attendance requirements during the pandemic (Durrani et al, 2021).…”
Section: Country Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, the SDGs provide a blueprint or roadmap for directing transitions of STSs to more sustainable outcomes. Exemplar cases include the study of SDG 9 goal of fostering innovation ecosystems to enable sustainability and inclusive growth in the Middle East and North Africa (MENA) region [12], and the monitoring of progress towards SDG 4 targets to determine how the education system manages to provide inclusive, equitable and effective pedagogy [13].…”
Section: Introductionmentioning
confidence: 99%